The molecular pathogenesis of triptolide-induced hepatotoxicity - Hu, Yeqing; Wu, Qiguo; Wang, Yulin; Zhang, Haibo; Liu, Xueying; Zhou, Hua; Yang, Tao (Frontiers in Pharmacology, 2022)
Triptolide (TP) is the major pharmacologically active ingredient and toxic component of Tripterygium wilfordii Hook. f. However, its clinical potential is limited by a narrow therapeutic window and multiple organ toxicity, especially hepatotoxicity. Furthermore, TP hepatotoxicity shows significant inter-individual variability. Over the past few decades, research has been devoted to the study of TP-induced hepatotoxicity and its mechanism. In this review, we summarized the mechanism of TP-induced hepatotoxicity. Studies have demonstrated that TP hepatotoxicity is associated with CYP450s, P-glycoprotein (P-gp), oxidative stress, excessive autophagy, apoptosis, metabolic disorders, immunity, and the gut microbiota. These new findings provide a comprehensive understanding of TP-induced hepatotoxicity and detoxification.